JBP485, A Dual Inhibitor of Organic Anion Transporters (OATs) and Renal Dehydropeptidase-I (DHP-I), Protects Against Imipenem-Induced Nephrotoxicity - Wang, Chong; Wang, Changyuan; Wu, Jingjing; Meng, Qiang; Jin, Huan; Sun, Huijun; Kaku, Taiichi; Chen, Jing; Huo, Xiaokui; Liu, Kexin (Frontiers in Pharmacology, 2022)
Imipenem (IMP) possesses a broad spectrum of antibacterial activity; however, nephrotoxicity limits its clinical application in patients with renal insufficiency. In our previous studies, a dipeptide, JBP485 (Cyclo-trans-4-L-hydroxyprolyl-L-serine), was found to attenuate drug-induced kidney injury. The current study aimed to explore whether JBP485 could relieve IMP-induced kidney injury and clarify the potential molecular pharmacokinetic mechanism. The effects of JBP485 on IMP nephrotoxicity were evaluated in rabbits and human kidney 2 (HK-2) cells. Drug-drug interactions (DDIs) mediated by organic anion transporters (OATs) and dehydropeptidase-I (DHP-I) were explored through pharmacokinetic studies in rats, metabolism assays in the kidney, and uptake studies in OAT-over-expressing cells. The results revealed that JBP485 significantly ameliorated IMP-induced nephrotoxicity in rabbits. Further, incubation of HK-2 cells with JBP485 or Cilastatin markedly improved the cell survival rate, inhibited apoptosis and attenuated mitochondrial damage by improving the stability of IMP and reducing its intracellular accumulation. This suggests that DHP-I and OATs might be involved in the protective effect of JBP485. Furthermore, coadministration with JBP485 significantly increased the plasma concentration and the area under the plasma concentration-time curve (AUC) of IMP, while decreasing IMP renal clearance and cumulative urinary excretion. Moreover, JBP485 reduced IMP uptake in kidney slices and OAT1/3-human embryonic kidney 293 (HEK293) cells. At the same time, the metabolism of IMP by DHP-I was inhibited by JBP485 with an IC50 value of 12.15 ± 1.22 μM. Finally, the molecular docking assay revealed a direct interaction between JBP485 and OAT1/3 or DHP-I. In conclusion, JBP485 protected against IMP nephrotoxicity in rabbits and HK-2 cells by improving IMP stability and reducing its intracellular accumulation via simultaneous inhibition of renal OATs and DHP-I. JBP485 is a promising renoprotective agent and could serve as an effective supplement to reduce IMP-induced adverse renal reactions in the clinical setting.